Legal Protection for Vaccine Recipients Covid-19 in Indonesia - Abdi, Muhammad Mahendra (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Regulation of the Minister of Health of the Republic of Indonesia Number 10 of 2021 concerning the Implementation of Vaccination in the Context of Combating the Corona Virus Disease 2019 (COVID-19) Pandemic, this Minister of Health Regulation is a government step in carrying out the legality of administering the COVID-19 vaccine because the spread of the COVID-19 virus is very fast. Occurs in humans, thus creating great concern for human life because it can lead to death. Therefore, the government took a response action by providing vaccinations for the people of Indonesia, the purpose of this vaccination is to overcome the high spread of COVID-19, the provision of the covid-19 vaccine given to the Indonesian people must also fulfill the proper rights for the recipients of the COVID-19 vaccine, so that when there is an impact on the administration of the Covid-19 vaccine, the government can handle it quickly. The problems in this paper are how is legal protection for people who receive the COVID-19 vaccine, the extent to which the government provides legal protection rights to people who receive the COVID-19 vaccine.